Pelatihan Penulisan Artikel Bagi Guru-Guru di SMP Negeri 1 Muaro Jambi - Sadikin, Ali; Siburian, Jodion; Mardiyanti , Lely; Astriawati , Fitri; Mursyd, Danial (Laboratorium Pembelajaran FKIP Universitas Jambi, 2024)
Writing scientific articles is important for teachers to increase professionalism. Every time you teach in class, there are certainly many problems that can be researched and produce written work. The service method is carried out using the lecture method, followed by the practice of writing articles using AI assistance. As a result of service activities, teachers gain knowledge and skills in writing scientific articles. They are enthusiastic about using AI in creating articles.The Community Service Program (PPM) for article writing was conducted at SMP N 1 Muaro Jambi, involving 28 teachers from various subject areas. The training began with the presentation of materials, followed by practical sessions and a Q&A segment. The teachers were enthusiastic about participating in the training, particularly in utilizing AI to assist in writing articles. Abstrak. Penulisan artikel ilmiah penting bagi guru untuk meningkatkan profesionalisme. Setiap kali mengajar dikelas tentu banyak persoalan yang dapat diteliti dan menghasilkan sebuah karya tulis. Metode pengabdian dilaksanakan dengan metode ceramah, dilanjutkan dengan praktek penulisan artikel dengan menggunakan bantuan AI. Hasil kegiatan pengabdian guru-guru memperoleh pengatahuan dan keterampilan dalam menulis artikel ilmiah. Mereka antusias dalam menggunakan AI dalam membuat artikel. Kegiatan PPM penulisan artikel dilaksanakan di SMP N 1 Muaro Jambi yang diikuti oleh 28 orang guru dari bermacam bidang studi. Pelatihan diawali dengan pemaparan materi, praktek, dan tanya jawab. Guru-guru antusias mengikuti pelatihan, terutama dalam penggunaan AI untuk membantu penulisan artikel.